Respons Dua Varietas Kedelai (Glycine max (L.) Merrill.)pada Pemberian Pupuk Hayati dan NPK Majemuk - Dewi Ratnasari; Mbue Kata Bangun; Revandi Iskandar M. Damanik (Jurnal Agroekoteknologi, 2015)
The objective of this research was to study the response of two soybean varieties growth and yieldon the biofertilizer and NPK compound fertilizer application. The factorial randomized blockdesign was used in this research with three factors i.e. : varety (Anjasmoro and Grobogan),biofertilizer    (0, 50 and 100 kg/ha) and NPK fertilizer (0, 125, and 250 kg/ha). This research wasconducted on the experimental field of North Sumatera University from April to August 2014. Theresults showed that varieties significantly affected the plant height (2, 3, 4 and 6 weeks planted, theleaf greeness level, time of flowering, the time of harvest, the number of productive branches, thenumber of pods per sample, the number of seeds per sample and the dry weight of 100 seeds.Biofertilizer unsignificantly affected on all parametres. The NPK compound fertilizer significantlyaffected the the plant height 5 weeks planted, the leaf greeness level and the number of seeds persample. The interraction between variety and biofertilizer singnificantly affected the time offlowering, however the interraction between variety and NPK fertilizer affected the time of flowering and the number of seeds per sample.Keywords: soybean, variety, biofertilizer and NPK fertilizer.